Identification of Modulators That Activate the Constitutive Androstane Receptor From the Tox21 10K Compound Library. (22nd September 2018) - Lynch, Caitlin; Mackowiak, Bryan; Huang, Ruili; Li, Linhao; Heyward, Scott; Sakamuru, Srilatha; Wang, Hongbing; Xia, Menghang
Abstract: The constitutive androstane receptor (CAR; NR1I3) is a nuclear receptor involved in all phases of drug metabolism and disposition. However, recently it's been implicated in energy metabolism, tumor progression, and cancer therapy as well. It is, therefore, important to identify compounds that induce human CAR (hCAR) activation to predict drug-drug interactions and potential therapeutic usage. In this study, we screen the Tox21 10, 000 compound collection to characterize hCAR activators. A potential novel structural cluster of compounds was identified, which included nitazoxanide and tenonitrozole, whereas known structural clusters, such as flavones and prazoles, were also detected. Four compounds, neticonazole, diphenamid, phenothrin, and rimcazole, have been identified as novel hCAR activators, one of which, rimcazole, shows potential selectivity toward hCAR over its sister receptor, the pregnane X receptor (PXR). All 4 compounds translocated hCAR from the cytoplasm into the nucleus demonstrating the first step to CAR activation. Profiling these compounds as hCAR activators would enable an estimation of drug-drug interactions, as well as identify prospective therapeutically beneficial drugs.